Nutshell ebook A novel. - McEwan, Ian (2016)
NATIONAL BESTSELLER • A “suspenseful, dazzlingly clever and gravely profound” ( The Washington Post ) novel that brilliantly recasts Shakespeare and lends new weight to the age-old question of Hamlet's hesitation, from the Booker Prize winner and bestselling author of Atonement. Trudy has been unfaithful to her husband, John. What’s more, she has kicked him out of their marital home, a valuable old London town house, and in his place is his own brother, the profoundly banal Claude. The illicit couple have hatched a scheme to rid themselves of her inconvenient husband forever. But there is a witness to their plot: the inquisitive, nine-month-old resident of Trudy’s womb. As Trudy’s unborn son listens, bound within her body, to his mother and his uncle’s murderous plans, he gives us a truly new perspective on our world, seen from the confines of his.